In Vivo Self-Assembly Nanotechnology for Biomedical Applications (Nanomedicine and Nanotoxicology, 2018)
This book reviews and discusses the development of self-assembled nanomaterials applied in biomedical fields. Based on self-assembled nanomaterial constructions, it highlights the mechanisms of the stimuli-response-induced assembly/disassembly and transformation. Moreover, it examines healthcare-related diseases, the applications of nanomaterials and therapy/detection strategies, providing readers with both a deeper understanding of the subject and inspirations for future research. The book is primarily intended for researchers and graduate students in the fields of material sciences and chemistry who wish to learn about the principles, methods, mechanisms and biomedical applications of self-assembled nanomaterials.